2021
DOI: 10.1159/000518099
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Renin Activity Predicts Prognosis and Liver Disease-Related Events in Liver Cirrhosis Patients with Ascites Treated by Tolvaptan

Abstract: <b><i>Background and Aims:</i></b> A retrospective study was to analyze the association of plasma renin activity (PRA) with overall survival and liver disease-related events in decompensated liver cirrhosis with ascites treated by tolvaptan. <b><i>Methods:</i></b> We included 196 patients with decompensated cirrhosis treated with tolvaptan and for whom hepatic ascites had remained uncontrolled by conventional diuretics. Factors associated with prognosis and appea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Numerous current studies continue to associate renin with poor outcomes. In large human observational studies of cirrhosis, plasma renin levels have been found as independent risk factors for the first decompensation event, hyponatremia, hypotension, and mortality [ 57 , 69 , 73 , 74 ]. Renin levels, like Ang1–7 levels, even correlated with MELD score in a small human study [ 57 ].…”
Section: Ras In Cirrhosis Portal Htn and The Development Of A Hyperdy...mentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous current studies continue to associate renin with poor outcomes. In large human observational studies of cirrhosis, plasma renin levels have been found as independent risk factors for the first decompensation event, hyponatremia, hypotension, and mortality [ 57 , 69 , 73 , 74 ]. Renin levels, like Ang1–7 levels, even correlated with MELD score in a small human study [ 57 ].…”
Section: Ras In Cirrhosis Portal Htn and The Development Of A Hyperdy...mentioning
confidence: 99%
“…While plasma renin levels are not routinely measured in the clinical setting, these recent findings present an avenue for improving clinical care. However, their utility is likely confounded by the frequent use of loop diuretics, mineralocorticoid receptor antagonists, ACEi, and ARBs in this population (whether specifically for the underlying liver disease or non-hepatic co-morbidities) [ 73 , 75 ]. Clinicians would also face challenges in interpreting one-time plasma renin levels of individual patients with cirrhosis, particularly considering the predicted difficulty of standardizing reference ranges.…”
Section: Ras In Cirrhosis Portal Htn and The Development Of A Hyperdy...mentioning
confidence: 99%
“…Splanchnic and peripheral vasodilation in response to excess nitric oxide stimulate the renin-angiotensin-aldosterone and sympathetic nervous systems, triggering a number of mechanisms that further exacerbate portal hypertension. Mediators of these pathways have been directly linked to mortality in patients with cirrhosis[ 76 , 77 ]. Thus, a number of drugs which attenuate the RAAS have been evaluated with mixed results.…”
Section: Emerging Therapies To Prevent Hepatic Decompensationmentioning
confidence: 99%